The Influence of Autocratic Leadership Style and Work Motivation on Turnover Intention in Shoe Factories in Cirebon - Abdurrokhim Abdurrokhim; Siti Maryam (Interdisciplinary Social Studies, 2026)
This study aims to analyze the influence of autocratic leadership style and work motivation on turnover intention in shoe factory employees in Cirebon. The high rate of employee turnover is a phenomenon that needs to be studied more deeply, especially in relation to leadership practices and work motivation levels. This study used a quantitative method, involving selected production employees using the total sampling technique. Data collection was carried out through an online questionnaire measured by the Likert scale, and analyzed using multiple linear regression. The results of the study showed that autocratic leadership style had a positive and significant effect on turnover intention, which means that the higher the level of autocratic leadership, the higher the employee's intention to leave. Work motivation has a negative and significant effect on turnover intention, which shows that the higher the work motivation, the lower the turnover intention. Simultaneously, autocratic leadership styles and work motivation have a significant effect on turnover intention. This study confirms that the transformation of leadership styles towards a more participatory approach and increased work motivation is an important strategy in reducing employee turnover intention in the manufacturing industry.